Hipnosis Lima Jari Kombinasi Instrumen Musik Pop Menurunkan Kecemasan Wanita Produktif Dimasa Pandemi Covid-19 - Putu Agus Ariana; Putu Indah Sintya Dewi; I Dewa Ayu Rismayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine differences in anxiety among productive women during the COVID-19 pandemic before and after being given five-finger hypnosis with a combination of pop music instruments in Bengkala Village, Buleleng Regency, Bali. This research method is quantitative research with a pre-experimental design, one group pre-post test design. In the univariate analysis of 20 respondents before being given intervention, the average anxiety score obtained was 20.85, with the lowest anxiety score, 15 or mild anxiety, and the highest score was 27 or moderate pressure. After being given the intervention, the average anxiety score obtained was 16.95, with the lowest anxiety score was ten or not anxious, and the highest was 25 or moderate anxiety. The results of the bivariate analysis showed that p-value = 0.005. In conclusion, the five finger hypnosis combination of pop music instruments effectively reduces pressure in productive women during the COVID-19 pandemic in Bengkala Village, Buleleng Regency, Bali. Keywords: Five Finger Hypnosis, Pop Music, Women